IDENTIFIKASI FAUNA TANAH EPIGEON DAN HEMIEDAFON PADA SISTEM TUMPANGSARI TANAMAN JAGUNG (Zea mays L.) DAN KACANG TANAH (Arachis hypogaea L.) PADA PERLAKUAN MIKORIZA INDIGEN DAN PUPUK ORGANIK CAIR - Pakki, Terry; Halim, Halim; Arbiyanti, Arbiyanti (Jurnal Agroteknos, 2012)
This study aimed to determine the effect of indigenous mycorrhiza and liquid organic fertilizer on corn and peanut intercropping system and its effect on the epigeon and hemiedafon fauna population. This study was conducted by using three methods of sampling: pitfall trap, transect and funnel barlles. The result of this study showed that there were several types of epigeon and hemiedafon soil fauna to the corn and peanut intercropping system that treated by indigenous mycorhiza and liquid organic fertilizer : they were Cockroachest east (Blatta orientalis L.), Millipedes (Trigoniulus corallinus), Leech (Tyrnnobdella rex), Black fire ants (Selenopsis richteri), Fire ants (Selenopsis geminata), Black ants (Dolichoderus bituberculatus), Centipede (Scolopendra sp.), Small red ants, Crickets ground (Allonemobius fasiatus), Field crickets (Gryllus pennsylvanicus), Ground spider (Lycosa sp.), German roaches (Blattella fasciatus), Termites (Coptotermes sp.), Snails (Achatina fulica) and Earthworm genus Lumbricus. The highest level of epigeon and hemiedafon soil fauna population was found at 4 MST; they were Black ants (Dolichoderus bituberculatus) and Termites (Coptotermes sp.) in one colony. The lowest level of epigeon and hemiedafon soil fauna population was found in untreated area (controlled). Key words : soil fauna, epigeon, hemiedafon, intercropping system, indigen mycorrhiza, liquid organic fertilizer